Scan-to-HBIM: automated transformation of point clouds into 3D BIM models for the digitization and preservation of historic buildings - Pablo Ariel Escudero (Vitruvio: International Journal of Architectural Technology and Sustainability)
Three-dimensional digital models of historical buildings must seamlessly integrate a wide array of data from diverse sources, including point clouds, alphanumeric information, 2D and 3D representations, BIM, GIS, images, sensor data, and real-time information streams, among other heterogeneous resources. Centralizing and presenting this multifaceted information cohesively is fundamental for fostering a comprehensive understanding and analysis of these historical monuments. In this context, the article introduces an automated process (Scan-to-HBIM) tailored specifically to transform point clouds into threedimensional models within BIM environments. This innovative approach not only enhances the accuracy in representing historic buildings but also significantly amplifies the level of detail (LoD), enabling a more nuanced representation of architectural structures. The article delves into the Scan-to-HBIM process, elucidating its relevance in the broader context of digitization and preservation of historic buildings, with a particular focus on its application to a sample point cloud. Furthermore, it underscores the pivotal advantages of this approach, emphasizing its proficiency in managing diverse datasets, elevating the level of detail, and exploring practical applications in both BIM and GIS realms.